Pablo Neruda : Nobel prize-winning poet - Goodnough, David (Springfield, NJ : Enslow Publishers, 1998)
Traces the life and career, including the political activities, of the famous Chilean poet.
Includes bibliographical references and index.
Keywords: Neruda, Pablo, -- 1904-1973 -- Juvenile literature; Poets, Chilean -- 20th century -- Biography -- Juvenile literature; Poets, Chilean -- Juvenile literature